Molecular characterization of Salmonella isolates recovered from slaughtered poultry in Trinidad. Issue 12 (16th September 2020) - Kumar, Nitu; Mohan, Krishna; Georges, Karla; Dziva, Francis; Adesiyun, Abiodun A.
Abstract: The study determined the genetic relatedness of Salmonella serotypes isolated from poultry ceca at the outlets cottage processors in Trinidad by pulsed‐field gel electrophoresis (PFGE). Of a total of 1503 cecal samples tested 91 (6.1%) yielded Salmonella spp. Ten serotypes were detected in the 91 Salmonella isolates which were digested by Xbal and subjected to PFGE. Based on the similarity of the PFGE patterns and the number of isolates exhibiting pulsotypes, five serotypes were selected for dendrogram analysis. Genetic diversity was common in the five serotypes of Salmonella studied which ranged from medium diversity (DI of 0.50) in serotype Typhimurium to complete diversity (DI of 1.00) found in Group B and subspecies Enterica 1 strains. It was concluded that conventional serotyping of Salmonella spp. as practiced in Trinidad has low discriminatory power compared to a combination of PFGE, dendrogram analysis, and diversity calculation used in the study, with epidemiological implications. Practical applications: The study used molecular methods to investigate the diversity in isolates that belonged to the same serotypes using PFGE pulsotypes and dendrogram analysis of PFGE patterns. In addition to the determination of percent similarities identified by the dendrogram, Simpson's diversity index indicated complete diversity in the pulsotypes of Salmonella isolates that belonged to serotypes S. Group B and S. subspecies Enterica 1. There was variation within the serotypes and the association of the PFGE pulsotypes with the patterns of resistance genes and virulence genes. Overall, serotyping of Salmonella to investigate the relatedness of isolates is inadequate and a combination of PFGE pattern, dendrogram analysis, and determination of diversity index offered a significantly better strategy to determine the relatedness and diversity of Salmonella isolates from poultry.